TRANSFORMASI KEPEMIMPINAN NASIONAL AKIBAT PENGARUH BUDAYA ASING DI MASA DEPAN - Abdu Rafi Ramadhan (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
This study examines how the penetration of foreign culture shapes Indonesia’s national leadership patterns amid globalization, focusing on shifts in values, power orientation, and the leadership styles of the young generation. Em_ploying a descriptive-qualitative approach, data were collected through literature review, in-depth interviews, and limited observation. The findings indicate that exposure to foreign culture especially through social media and international education has influenced the communication styles and outlooks of prospective national leaders. Most respondents observed a shift toward more inclusive, rational, and efficiency-oriented leadership, while expressing concern over the erosion of local values such as gotong royong (mutual cooperation) and musyawarah (deliberation). The research also reveals the emergence of a hybrid leadership model that blends global principles with local wisdom. Consequently, selective filtering of foreign cultural influences and the strengthening of character and cultural education in leadership development programs are essential to preserve Indonesia’s leadership identity amid global modernization.